The Use of Storybird to Improve Students’ Narrative Writing Skills: A Classroom Action Research in Grade VIII at SMP N 3 Sleman, Yogyakarta - Linda Nur Ainah; Jamilah (Yayasan Ilomata, 2026)
This study investigates the use of the Storybird platform to enhance the writing skills of grade VIII students at SMP N 3 Sleman in the 2024/2025 academic year. Although digital storytelling tools are increasingly integrated into EFL pedagogy, empirical evidence regarding their classroom implementation for improving multiple dimensions of writing remains limited. Addressing this gap, the research examines how Storybird supports students’ writing development in a real classroom context. Employing a classroom action research design conducted in two cycles, the researcher collaborated with an English teacher. Participants comprised 32 students from class VIII B. Data were gathered through writing tests, observation sheets, field notes, and semi-structured interviews. Qualitative data underwent thematic analysis, while quantitative data were analyzed using descriptive statistics. Validity was established through democratic, dialogic, catalytic, and outcome criteria. Findings indicate that Storybird’s picture book feature facilitated improved idea generation and more coherent organization of narrative texts. Qualitative evidence revealed heightened engagement, better vocabulary selection, and gradual gains in grammatical accuracy. Quantitatively, mean writing scores rose from 57.61 in the pre-test to 71.50 in Cycle 1 and 80.03 in Cycle 2. These results suggest that Storybird was associated with enhanced writing performance among the students. Given the classroom action research design, causal inferences must be drawn cautiously. Nevertheless, the study contributes contextual evidence on the pedagogical value of digital storytelling tools for supporting writing development in resource-constrained EFL settings.